2020
DOI: 10.1088/1361-6382/ab79d5
|View full text |Cite
|
Sign up to set email alerts
|

Analytic solutions for parallel transport along generic bound geodesics in Kerr spacetime

Abstract: We provide analytical closed form solutions for the parallel transport along a bound geodesic in Kerr spacetime. This can be considered the lowest order approximation for the motion a spinning black hole in an extreme mass-ratio inspiral.As an illustration of the usefulness of our new found expressions we scope out the locations of spin-spin resonances in quasi-circular EMRIs. All solutions are given as functions of Mino time, which facilitates the decoupling of the equations of motion. To help physical interp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
(63 reference statements)
0
22
0
Order By: Relevance
“…We begin by discussing bound Kerr geodesics. The most important aspects of this content are discussed in depth elsewhere [24][25][26][27][28]; we briefly review this material for this paper to be self contained, as well as to introduce notation and conventions that we use. Certain lengthy but important formulas are given in Appendix A.…”
Section: Kerr Geodesicsmentioning
confidence: 99%
See 3 more Smart Citations
“…We begin by discussing bound Kerr geodesics. The most important aspects of this content are discussed in depth elsewhere [24][25][26][27][28]; we briefly review this material for this paper to be self contained, as well as to introduce notation and conventions that we use. Certain lengthy but important formulas are given in Appendix A.…”
Section: Kerr Geodesicsmentioning
confidence: 99%
“…We have found that x I ≡ cos I is a particularly good parameter to describe inclination: x I varies smoothly from 1 to −1 as orbits vary from prograde equatorial to retrograde equatorial, with L z having the same sign as x I . Schmidt [25] first showed how to compute (E, L z , Q) for generic Kerr orbits; a particularly clean representation is provided by van de Meent [28]. We summarize his formulas in Appendix A, tweaking them slightly to use our preferred parameter set (p, e, x I ).…”
Section: 15)mentioning
confidence: 99%
See 2 more Smart Citations
“…In the last two years, several novel analytic results on Kerr geodesics were achieved [40,41,[51][52][53][54][55][56][57][58][59][60]. Explicitly real, fully explicit, "initial data-dependent" analytical solutions in terms of elliptic functions were given for (i) radial and polar motion for timelike bounded orbits [52]; (ii) generic (i.e. excluding zero measure sets) polar motion for null or timelike orbits [40,41]; (iii) generic radial motion for null orbits [53] and (iv) general (i.e.…”
Section: Introductionmentioning
confidence: 99%